PATIENT SAFETY IN THE HOSPITAL ENVIRONMENT: MULTIPROFESSIONAL HEALTH CARE - Carolina Salustino dos Santos, Maria; Emília Araújo de Oliveira, Ana; Carvalho Lima, Raquel; Vitória Gomes Lins Paz, Iracema; Marília Lima Guida, Vânia; Figueiredo da Silva, Yasmin; Karine de Assunção Almeida, Anne; Allyson Gomes Ferreira, Jefferson; de Lucena Viana Alves, Letícia; Claudino do Nascimento, Nathalia; Lima Silva, Luciene; Maria Bezerra, Lucrécia; et al. (Health and Society, 2022)
Patient safety means acting with skill, responsibility, humanization and commitment to the patient’s health, with the main focus of offering safe care, with a reduction in incidents. The objective is: To verify publications on patient safety and care shared in a multiprofessional way in the hospital environment. This study is an integrative literature review, with a qualitative and exploratory approach, which carried out research in the following health databases: Latin American and Caribbean Literature on Health Sciences (LILACS); Online Scientific Electronic Library (SciELO); Medical Literature Review (MEDLINE/PUBMED). The research gathered 8 articles on the topic. Through the analysis of the results, it was observed that there is a great importance of communication and union between the members of the hospital team, especially in relation to the exchange of information, in order to prevent errors and exposures from occurring to the patient.